A multilevel model of organizational learning: Incorporating employee spontaneous workplace behaviors, leadership capital and knowledge management. Issue 2 (31st December 2018) - Chou, Shih Yung; Ramser, Charles
Abstract : Purpose: Organizational learning has long been recognized as an important determinant of organizational performance and sustainability. Existing research, however, has commonly viewed organizational learning as a single-level, top-down and organized organizational event initiated by the leader. This particular perspective may fall short of explaining the effect of employee spontaneous workplace behaviors on organizational learning. Thus, the purpose of this paper is to develop a multilevel theoretical model exploring how an employee's upward helping and voice behavior foster organizational learning through developing leadership capital. Design/methodology/approach: A conceptual analysis was conducted by incorporating relevant research. Findings: This paper proposes the following. First, an employee's upward helping increases a leader's human capital and social capital. Second, the leader's human capital and social capital enhance the employee's psychological empowerment and knowledge leadership. Third, the employee's psychological empowerment leads to employee voice behavior. Fourth, employee voice behavior strengthens knowledge leadership. Finally, knowledge leadership promotes organizational learning. Originality/value: This paper provides a theoretical framework for future research attempting to understand organizational learning from a multilevel, bottom-up perspective. Practically, this paper offers several implications that help promote organizational learning through encouraging employee upward helping and voice behavior.